(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
At the Site-1, net primary productivity ranged 3850 mg C/m2/day with an annual mean±S.D. of 2769.76±983.64mg C/m2/day . Maximum NPP (4150 mg C/m2/day) was recorded during February and minimum (400 mg C/m2/day) in May .Net primary productivity in the Site-2 ranged 5200 mg C/m2/day with an annual mean±S.D. of 2231.26±1202.1 mg C/m2/day .Maximum NPP (5200 mg C/m2/day) was observed in February and minimum (0 mg C/m2/day) in August. Community respiration at the Site-1 ranged 2575 mg C/m2/day with an annual mean ±S.D. of 6618.76±626.91 mg C/m2/day .Maximum community respiration (2650 mg C/m2/day) was recorded during October and minimum (76mg C/m2/day) in August . At the Site-2 community respiration ranged 3625 mg C/m2/day with an annual mean ±S.D. of 2331.26±887.21mg C/m2/day. Maximum community respiration (3775 mg C/m2/day) was observed in October and minimum (250 mg C/m2/day) in May.